Pollination of oil palm by weevils in Southern Bahia, Brazil - Moura, José Inácio Lacerda; Cividanes, Francisco Jorge; Filho, Lindolfo Pereira dos Santos; Valle, Raul Rene (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to determine the fertilization rate of oil palm trees, after the introduction of Elaeidobius kamerunicus in Southern Bahia, Brazil, and the population fluctuation, spatial distribution and the influence of meteorological factors on E. kamerunicus and E. subvittatus. Physical analyses of 12 thousand oil palm spikelets were accomplished during 2004–2006. Pearson correlation was used to evaluate the relation between monthly average temperatures and monthly totals of E. kamerunicus and E. subvittatus individuals. The fertilization rate was 79.4%, an increase of 19% when compared to palm trees pollinated only by E. subvittatus. Commercial plantations of oil palm, in Ituberá and Nazaré, BA, presented 76% mean rates of fertilization. E. kamerunicus was the dominant species in the plantations of Una, BA. Populations of E. kamerunicus overwhelmed E. subvittatus ones in all the municipalities where there are great areas of subspontaneous palm oil. However, in Itapebi, BA, populations of E. subvittatus exceeded those of E. kamerunicus. Temperature and rainfall affected the flight activity and the population density of E. subvittatus.